Indian economic growth: Lessons for the emerging economies - Suparna Chakraborty (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Can we use neoclassical growth model to single out the important transmission channels through which external factors or primitives affected the Indian economy and caused the remarkable growth of the period 1982-2002? In this paper, we answer the question by applying the new technique of business cycle accounting to the Indian economy. Our results show us that the primary conduit of policies that brought about significant growth in India was productivity that registered an unprecedented increase particularly in the 1990s. Our results further indicate that changes in labour market frictions and investment market frictions did not play a significant role, though increased government consumption aided growth by propping up demand. In addition, we examine the effective tax rates in India and find that while investment taxes barely fluctuated, income tax rates were increasing throughout. We suspect other positive developments in the Indian economy overwhelmed the negative effect of increasing labour income taxes on growth. Our result suggests that any emerging country that aims to replicate the Indian experience would do well to formulate policies that target productivity, a lesson that seems consistent with the Japanese experience since the Second World War.
Keywords: E13; E32; 330; business cycle accounting; India; growth; wedges; neoclassical growth; taxes; Wirtschaftswachstum; Neoklassik; Konjunktur; Indien